Psoriasis. Diagnostic and therapeutic recommendations of the Polish Dermatological Society. Part 2 - Adam Reich; Zygmunt Adamski; Grażyna Chodorowska; Andrzej Kaszuba; Dorota Krasowska; Aleksandra Lesiak; Joanna Maj; Joanna Narbutt; Agnieszka J. Osmola-Mańkowska; Agnieszka Owczarczyk-Saczonek; Witold Owczarek; Waldemar J. Placek; et al. (Termedia Publishing House, 2020)
Psoriasis is one of the most common chronic inflammatory dermatoses. We present the second part of the diagnostic and therapeutic guidelines on psoriasis. The second part discusses the principles of treatment of plaque psoriasis, with a particular emphasis on systemic drugs. The second part of the guidelines constitutes an integral whole with the first part which addresses the general principles of diagnostic management, prevention of cardiovascular complications, therapeutic goals, and selected specific forms of psoriasis. The guidelines have been updated to take account of access to new therapies which have recently been approved in Poland, ongoing improvements in the efficacy of available therapeutic methods, and changing needs of patients. We hope that the current guidelines will assist physicians in making diagnostic and therapeutic decisions, and contribute to the improvement of medical care provided to patients with psoriasis.